Genome Mining of Terpene Synthases from Fourteen Streptomyces Strains - Yuanyuan Li; Xi Xiang; Zhiyuan Ren; Rui Wang; Minghui Xie; Gen Li; Xiaohui Yan; Zhilong Zhao; Zixin Deng; Min Xu; Anwei Hou (Microorganisms, 2025)
Terpenoids are the most structurally diverse class of natural products (NPs). Despite their abundance, the functional diversity of bacterial terpene synthases (TPSs), particularly from Streptomyces species, remains largely unexplored. In this study, fourteen Streptomyces strains were subjected to genome sequencing and bioinformatic analysis to systematically mine class I TPSs. A total of forty-eight TPSs were identified and categorized through phylogenetic analysis, and five representative TPSs distantly related to known TPSs were selected for functional investigation. Biochemical assays revealed that TAC28_6116 is a sesquiterpene synthase producing thujopsan-2β-ol (1) and thujopsene (2), marking the first report of thujopsan-2β-ol production from a bacterial source. TAC49_7078 is a diterpene synthase responsible for the formation of ent-phomacta-1(15),3,7-triene (3). Notably, TAC43_2999 was identified as a novel sesterterpene synthase that produced compound 5 in vitro, while the generation of a previously undescribed compound 6, sestermalaysiene, was exclusively detected during in vivo fermentation using the engineered Escherichia coli chassis optimized for terpenoid biosynthesis. Structural elucidation of sestermalaysiene was supported by nuclear magnetic resonance (NMR) analysis and quantum chemical calculations. Its formation might proceed via a rare [4 + 2] cycloaddition mechanism. Overall, this work expands our knowledge of the catalytic diversity of bacterial TPSs and offers promising biocatalysts for terpenoid engineering and discovery.